Genetic Diversity, Chemical Components, and Property of Biomass Paris polyphylla var. yunnanensis - Zhou, Nong; Xu, Lingfeng; Park, Sun-Min; Ma, Ming-Guo; Choi, Sun-Eun; Si, Chuanling (Frontiers in Bioengineering and Biotechnology, 2021)
Paris polyphylla var. yunnanensis is a kind of biomass resource, which has important medicinal and economical value with huge market. This review paper aims to summary the recent development of biomass P. polyphylla var. yunnanensis. The genetic diversity and chemical components of biomass P. polyphylla var. yunnanensis were reviewed based on the literatures. Both the genetic diversity and genetic structure of biomass P. polyphylla var. yunnanensis were compared by means of molecular marker technologies. All the extraction processes, harvest time, and drying method on the chemical components were summarized in detail. The differences of arbuscular mycorrhizal fungi on the infection rate, diosgenin content, microorganisms, enzyme activities, rhizospheric environment, and endogenous hormones were discussed. This review paper is beneficial to the applications of biomass P. polyphylla var. yunnanensis as a biomass resource in biomedical field.